Patients’ perception at a dental school clinic on the impact of Covid-19 on dental care (Research, Society and Development, 2022)
On March 11, 2020, the World Health Organization declared the global pandemic of Covid-19, caused by the coronavirus 2 (SARS-CoV-2), which causes an acute respiratory infection syndrome, quickly impacting health services around the world. world. So far, there are still few studies on the impact of the pandemic on dental treatments and, consequently, on the quality of life and health of these patients. The objective of this study is to evaluate the patient's perception of the impact of the Covid-19 pandemic on dental treatments performed at the dental clinic of Universidade Anhanguera Osasco. An observational study was carried out using a closed questionnaire applied to patients undergoing treatment in the waiting room. 165 patients were interviewed; and, despite the main reason that 44.2% of patients sought treatment due to toothache, 71.5% did not seek treatment before due to lack of financial condition, although 81.8% reported fear due to the pandemic. Approximately half of patients feel safe in the waiting room, but 47.9% feel partially safe in the office. In this way, understanding the patient's perception is important to improve reception processes and improve safety during the care of professors, students and patients in dental school clinics, since 63% of patients missed a scheduled appointment due to fear or fear of contagion during the pandemic.